Η σχέση μεταξύ της τεχνικής αποτελεσματικότητας στον γεωργικό τομέα και του επιπέδου ανάπτυξης: μια εμπειρική διερεύνηση σε δείγμα αναπτυγμένων και λιγότερο αναπτυγμένων χωρών - Ρέππας Παναγιώτης Α.; Χριστόπουλος Δημήτριος Κ.; Αράπογλου Βασίλης Π. (SPOUDAI Journal of Economics and Business, 1999)
The primary objective of this paper is to obtain estimates of country-specific technical efficiency in agriculture and to asses the relationship between technical efficiency in agriculture and level of development. For this reason, inter-country data for 33 development and less developed countries are used. The measures of technical efficiency are calculated from the residuals of a stochastic frontier production function. The results show that there is in most cases a positive relationship between technical efficiency in agriculture and level of development.